Pemeriksaan Periodik Pada Rangkaian Instalasi Listrik Bangunan Untuk Mencegah Bencana Kebakaran Melalui Penambahan Prosedur Pada SOP Penerbitan SLO Dari PLN - Eddy Lybrech Talakua (Dewan Pimpinan Daerah (DPD) Perkumpulan Dosen Indonesia Semesta (DIS) Jawa Timur, 2021)
Electric short circuit which causes fire disaster is still a major factor. The average percentage of fires due to electricity reached 70% of the total cases in the capital city of Jakarta for the period 2000 to 2018. Intentional or unintentional deviant behavior committed by electricity users through efforts to reduce the quality of electrical installations is an opportunity for fires. The use of sophisticated electrical equipment and general regulations for electrical installations (PUIL) still cannot guarantee that a fire will not occur. This problem arises because PLN has only used the KWH meter and current limiter (MCB) for electricity consumers to date. Misuse of electrical installations occurs when the handover process of electrical installation work has been carried out, thus it can be concluded that the problem is based more on the behavior of electricity consumers. In order to avoid this bad behavior, prevention efforts need to be made through the application of a periodic inspection system on building electrical installations that have been certified by SLO by a team in the form of PLN. In this article, it is proposed to add a procedure to the SOP for the issuance of the SLO certificate, namely periodic inspections of a series of building electrical installations.